HUBUNGAN ANTARA SEGMENTASI DEMOGRAFIS DENGAN KEPUTUSAN MENGGUNAKAN MEDIA SOSIAL - Erlangga, Rizky; Amidi, Amidi (Jurnal Ilmu Manajemen, 2019)
The problem formulation in this study was the relationship between demographic segmentation and the decision to use social media in Kelurahan 3-4 Ulu Palembang. The aim was to find out the relationship between demographic segmentation and the decision to use social media in Kelurahan 3-4 Ulu Palembang. This type of research was associative. The sample used was 235 people using a probability sampling technique. The data used in this study were primarily because they were obtained based on questionnaires distributed to respondents. The analysis technique used was quadratic Kai. The results of the study showed that there were indicators that indicated a relationship and there was no relationship between demographic segmentation and the decision to use social media in Kelurahan 3-4 Ulu Palembang. Indicators that showed the existence of a relationship were: (1) there was a sexual relationship based on the frequency of use. While indicators that did not show the existence of a relationship: (1) there was no sex relationship utilization (2) there was no relationship between types of employment in terms of use and utilization (3) there was no relationship between age of use and utilization (4) there was no relationship between income and utilization